Prenatal Alcohol and Neurologic Dysfunction - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Of 698 pregnant women interviewed about alcohol consumption at the maternity hospital in Roubaix, France, 156 of the offspring were investigated at age 4 and 1/2 years, using a standardized neuropsychological assessment.